Aplikasi Amelioran Tanah dan MycoSilvi pada Falcataria sp. dan Ochroma bicolor Rowlee. untuk Reklamasi Lahan Pascatambang Pasir Silika - Munawaroh, Khoryfatul; Budi, Sri Wilarso; Pamoengkas, Prijanto (Jurnal Ilmu Pertanian Indonesia, 2020)
Open pit mining of silica sand causes some soil degradations and environmental impacts, such as lowering soil pH, lowering soil fertility, soil compaction, and toxicity of micronutrients such as Al, Fe, and Zn. The aim of this study was to analyze the soil properties of land post mining of silica sand and to analyze the growth response of Falcataria sp. and Ochroma bicolor by combination of soil ameliorant and MycoSilvi. The experimental design was split plot design of two treatment factors, MycoSilvi and soil ameliorant. The main plot is MycoSilvi that consist of two levels (MycoSilvi and without MycoSilvi). The subplot is soil ameliorant that consisted of six levels (compost 0 g, lime 0 g; compost 0 g, lime 1.56 g; compost 0 g, lime 3.12; compost 9 g, lime 0 g; compost 9 g, lime 1.56 g; compost 9 g, lime 3.12 g). The results showed that the soil ameliorant (lime 3.12 g and compost 9 g) and MycoSilvi was the best treatment to increase height, diameter, biomass, and mycorrhizal colonization of Falcataria sp. and O. bicolor. Keywords: MycoSilvi, reclamation, soil ameliorant